2010
DOI: 10.1017/s1041610210000499
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine is associated with hippocampal and white matter atrophy in older subjects with mild hypertension

Abstract: In older hypertensives, plasma homocysteine levels are associated with increased rates of progressive white matter and hippocampal atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
(53 reference statements)
1
30
0
1
Order By: Relevance
“…This new cortical mapping study complements prior studies associating high levels of homocysteine with overall brain volume reduction, WM atrophy rate, baseline volume and atrophy rate of the hippocampus and medial temporal lobe (Clarke et al, 1998a, den Heijer et al, 2003, Douaud et al, 2013, Firbank et al, 2010, Williams et al, 2002), lower tissue volumes in frontal and parietal WM (Rajagopalan et al, 2011), greater cortical atrophy (den Heijer et al, 2003), longitudinal ventricular volume enlargement in elderly individuals with arteriosclerotic disease (Jochemsen et al, 2012), lower whole brain GM volume in non-demented elderly (Whalley et al, 2003) in humans and with lower GM volume and density in prefrontal cortices and striatum in rhesus monkeys (Willette et al, 2012). Our prior study in an almost entirely overlapping subject population – but with a different method, TBM – found WM tissue contraction (Rajagopalan et al, 2011) in areas that structurally connect the GM regions we see here in the cortex.…”
Section: Discussionsupporting
confidence: 64%
“…This new cortical mapping study complements prior studies associating high levels of homocysteine with overall brain volume reduction, WM atrophy rate, baseline volume and atrophy rate of the hippocampus and medial temporal lobe (Clarke et al, 1998a, den Heijer et al, 2003, Douaud et al, 2013, Firbank et al, 2010, Williams et al, 2002), lower tissue volumes in frontal and parietal WM (Rajagopalan et al, 2011), greater cortical atrophy (den Heijer et al, 2003), longitudinal ventricular volume enlargement in elderly individuals with arteriosclerotic disease (Jochemsen et al, 2012), lower whole brain GM volume in non-demented elderly (Whalley et al, 2003) in humans and with lower GM volume and density in prefrontal cortices and striatum in rhesus monkeys (Willette et al, 2012). Our prior study in an almost entirely overlapping subject population – but with a different method, TBM – found WM tissue contraction (Rajagopalan et al, 2011) in areas that structurally connect the GM regions we see here in the cortex.…”
Section: Discussionsupporting
confidence: 64%
“…HHCy is associated with an increased rate of hippocampal atrophy [16] and with accelerated cognitive decline in AD patients [88] and is now accepted as a risk factor for AD [6]. Plasma HCy concentration is strongly associated with hippocampal atrophy, white matter lesions and lacunar infarcts in cross-sectional studies [32,61,117,123]. The association with hippocampal atrophy appears to be independent of amyloid pathology [14].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that mild-moderate HHCy is a risk factor for SVD [32,44,45,61,61,62,117,123]. In case-control studies HHCy was positively-associated with SVD severity, with highest plasma total HCy concentration (plasma [HCy]; average 20 µM) in patients with confluent leukoaraiosis on MRI scans, indicative of more severe SVD [44,61].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are required to determine the mechanisms that might be responsible for homocysteine-related atrophy. In a separate paper we address the relationship between homocysteine concentrations on grey and white matter atrophy [23]. Our data strongly support the conduct of interventional studies to investigate the efficacy of homocysteine-lowering treatment (e.g.…”
Section: Discussionmentioning
confidence: 54%